AXIOLOGICAL COMPONENT OF GENRE LITERACY STRUCTURE OF FUTURE TEACHERS OF WORLD LITERATURE - Hrytsak, Natalia (Continuing Professional Education: Theory and Practice, 2020)
The article presents the author`s structure of genre literacy of future teachers of world literature that is a synthesis of interrelated components (informational, axiological, intercultural, and communicative-pragmatic). The importance of fiction researching in the content and form unity is emphasized as it contributes to an adequate interpretation of alien cultural work of fiction. The expediency of introducing axiological component into the structure of genre literacy future teachers of world literature is substantiated. The content of the axiological block of the structure of genre literacy of future world literature teachers is analyzed on the basis of literary studies, works on teaching methodology of Ukrainian and World literature, studies in philosophy, aesthetics, cultural studies and other social and humanities sciences. Especial attention is drawn on the issue of universal and national value dominants. The axiological component of the structure of genre literacy of world literature future teachers is aimed at awareness of the nature of fundamental values, conception of alien values, taking into account the heritage of the native culture, awareness of differences in the system of value orientations, awareness of national originality. Particular attention is paid to the concept of the phenomenon of values of the F. Kluckhohn and F. Strodtbeck. Students-philologists’ perception of these American scholars’ values orientation theory will help them to determine the nature of values, type and characteristics of culture. The article focuses on the problem of cultural shock. It is shown that the concept of dialogue of cultures helps to solve the outlined problem, and helps to understand the way of thinking of another people, let them build a strategy of intercultural dialogue. It has been proved that the perception of alien cultural values by the student-philologist is a creative process that involves an emotional adjustment to the reception of different cultural reality. It is emphasized that the axiological component of the structure of genre literacy of future teachers of world literature synthesizes the professional and personal growth of the student-philologist